2016
DOI: 10.1155/2016/7853424
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis RelatedABO,F5,MTHFR,andFGGGene Polymorphisms in Morbidly Obese Patients

Abstract: Objective. Obesity is a well-known risk factor for thrombotic complications. The aim of the present study was to determine the frequency of thrombosis related ABO, F5, MTHFR, and FGG gene polymorphisms in morbidly obese patients and compare them with the group of nonobese individuals. Methods. Gene polymorphisms were analyzed in 320 morbidly obese patients (BMI > 40 kg/m2) and 303 control individuals (BMI < 30 kg/m2) of European descent. ABO C>T (rs505922), F5 C>G (rs6427196), MTHFR C>T (rs1801133), and FGG C>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Besides known causes involved in overweight/ obesity development (poor eating habits, lack of physical activity, and psychological disorders), genetics plays a very important role, since it represents up to 70% of factors associated with overweight/obesity (4). The results of this study showed no statistical differences about the prevalence of the MTHFR 677C>T polymorphism between NW and overweight/obesity individuals, which agrees with the majority of researches (4, 8, 10, 11, 12, 14, 17, 18, 20, 22, 22, 29). However, opposite findings have also been described; so Lambrinoudaki et al (9) observed that healthy postmenopausal women carrying the 677CT or 677TT genotype had central adiposity and waist higher hip ratio compared with women carrying the 677CC genotype.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides known causes involved in overweight/ obesity development (poor eating habits, lack of physical activity, and psychological disorders), genetics plays a very important role, since it represents up to 70% of factors associated with overweight/obesity (4). The results of this study showed no statistical differences about the prevalence of the MTHFR 677C>T polymorphism between NW and overweight/obesity individuals, which agrees with the majority of researches (4, 8, 10, 11, 12, 14, 17, 18, 20, 22, 22, 29). However, opposite findings have also been described; so Lambrinoudaki et al (9) observed that healthy postmenopausal women carrying the 677CT or 677TT genotype had central adiposity and waist higher hip ratio compared with women carrying the 677CC genotype.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the 677T allele has been linked with overweight/obesity risk, dyslipidemias, and diabetes in several populations. However, so far, the studies have been controversial (4, 5, 7, 8, 9, 10, 11, 12, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30). Here, we analyzed whether there is an association of the MTHFR 677C>T polymorphism with overweight and obesity, as well as its relationship with lipid profile, glucose level, and anthropometric measurements in a young Mexican population.…”
Section: Introductionmentioning
confidence: 99%
“…The association between the CC genotype of MTHFR and WHR in the present study could be explained by an unequal distribution of overweight and obese subjects or the size sample; however, we did not observe significant differences in frequencies of the MTHFR genotypes between the subjects with normal and excessive body weight, which is in line with other studies. 32,35 Furthermore, because of contradictory results of other studies 35,36 concerning a relationship between MTHFR genotypes and anthropometric measurements, further analysis are still necessary to clarify the role of the MTHFR rs1801133 polymorphism in overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on literature, we tested the following thrombosisrelated genes: ABO, F5, F2, FGG, F11, PROC, STAB2, ZFPM2, TSPAN15, SLC44A2, PROCR, and STXBP5, which have been reported by two or more previous VTE genetic studies (Table S4). [8][9][10][11][12][13][14][18][19][20][21][22][23][24] We used all variants in and within 100 kb of each gene, and analyzed whether these variants were associated with post-OLT thrombosis after clumping. p-values of logistic regression were used to evaluate the included variants.…”
Section: Targeted Gene Checkmentioning
confidence: 99%
“…Continued)AJT pairs are described in Table1. Thrombotic cases included 60 recipients with HAT (5.5%), 25 recipients with PVT (2.3%), and 27 recipients with other thrombosis (2.5%), which occurred after a median of 7 days (IQR[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. During a median follow-up period of 9 years, of 922 (30.6%) recipients experienced graft loss and 143 recipients underwent retransplantation.…”
mentioning
confidence: 99%